The Dimensions of School Discipline: Toward a Comprehensive Framework for Measuring Discipline Patterns and Outcomes in Schools - Luis A. Rodriguez; Richard O. Welsh (SAGE Publishing, 2022)
The school discipline literature has expanded rapidly in recent decades, yet the conceptualization and measurement of school discipline patterns remains overlooked. In this paper, we present a comprehensive analytic framework to examine school discipline patterns that encompasses school-level metrics that capture the prevalence and disparity in exclusionary discipline and regression-based approaches that examine the likelihood that students experience exclusionary discipline. We apply the framework to New York City and, based on school-level metrics, find that Black students have the highest prevalence and the highest disproportionality. Results from regression models affirm that Black students are most likely to receive office discipline referrals and suspensions and experience differential processing of suspensions for similar categories of infractions. The findings illustrate the nuances of the disciplinary process in schools and inform the consideration of a range of available analytic tools that educational stakeholders may employ to better measure and understand exclusionary discipline.